Non-nucleoside hepatitis B virus polymerase inhibitors identified by an in vitro polymerase elongation assay - Nakajima, Shogo; Watashi, Koichi; Fukano, Kento; Tsukuda, Senko; Wakae, Kousho; Aizaki, Hideki; Muramatsu, Masamichi; Wakita, Takaji; Toyoda, Tetsuya (Journal of gastroenterology, 2020)
Background Hepatitis B virus (HBV) polymerase is the only virus-encoded enzyme essential for producing the HBV genome and is regarded as an attractive drug target. However, the difficulty of synthesizing and purifying recombinant HBV polymerase protein has hampered the development of new drugs targeting this enzyme, especially compounds unrelated to the nucleoside structure. We recently have developed a technique for the synthesis and purification of recombinant HBV polymerase containing the reverse transcriptase (RT) domain that carried DNA elongation activity in vitro. Methods We used the overproduced protein to establish an in vitro high-throughput screening system to identify compounds that inhibit the elongation activity of HBV polymerase. Results We screened 1120 compounds and identified a stilbene derivative, piceatannol, as a potential anti-HBV agent. Derivative analysis identified another stilbene derivative, PDM2, that was able to inhibit HBV replication with an IC 50 of 14.4 ± 7.7 μM. An infection experiment suggested that the compounds inhibit the replication of HBV rather than the entry process, as expected. Surface plasmon resonance analysis demonstrated a specific interaction between PDM2 and the RT domain. Importantly, PDM2 showed similar inhibitory activity against the replication of both wild-type HBV and a lamivudine/entecavir-resistant HBV variant. Furthermore, PDM2 showed an additive effect in combination with clinically used nucleos(t)ide analogs. Conclusions We report the development of a screening system that is useful for identifying non-nucleos(t)ide RT inhibitors.